Determination E-Tax System and Tax Incentive on MSMEs Taxpayer Compliance during Pandemic (Universitas Terbuka, 2023)
This study aims to ascertain the significant effect of the E-Tax System and Tax Incentive on increasing MSMEs taxpayer compliance during the Covid-19 pandemic in East Java, the E- Tax System and Tax Incentive on MSMEs taxpayer compliance during the East Java Covid-19 pandemic. This research uses the mixed method. Quantitative data collection methods and qualitative approaches to discuss the phenomenon of the state of individual taxpayers who use E- Tax, as well as fiscus as recipients and managers of E-Tax accounts. The research resulted in findings that there is a significant and positive relationship between the use of e-Billing on the use of e-SPT, the use of e-SPT on MSMEs Taxpayer Compliance, the use of Tax Incentive Facilities on the use of e-Billing, the use of Tax Incentive Facilities on the use of e-SPT, and the use of Tax Incentive Facilities on MSMEs Taxpayer Compliance. There is no relationship between the use of e-Billing and MSMEs Taxpayer Compliance. The main finding in this study is that there is a significant and positive relationship between the use of Tax Incentives on MSMEs Taxpayer Compliance through the use of e-Billing and e-SPT. This means that the increase in the use of Tax Incentives will also be followed by an increase in the use of e-Billing and e-SPT, and has an impact on increasing MSME Taxpayer Compliance. So it can be concluded from the findings stated that Tax Incentives Through the E-Tax System have a significant and positive relationship with MSME Taxpayer Compliance During the Covid-19 Pandemic in East Java.